Evaluation of the chromium-EDTA complex and creatinine as markers for urinary volume in cattle - Rodrigues, A. N. [UNESP]; Palma, M. N.N.; Rodrigues, J. P.P.; Oliveira, C. V.R.; Camacho, L. F.; Silva, T. E.; Rennó, L. N.; Detmann, E. (Taylor & Francis, 2023)
Creatinine and intravenously infused Cr-EDTA complex were compared as markers for urinary volume estimation in cattle fed diets containing different concentrate levels. Ten Nellore heifers were used in a two-period crossover design and fed with two diets of divergent maize silage to concentrate ratios (90:10 and 50:50). The urinary marker concentrations were strongly and positively associated with each other, and both correlated strongly and negatively with total urine volume. Creatinine excretion and chromium recovery did not vary according to diets, but chromium recovery exhibited a lower variance among animals. The evaluation of urine spot samples showed that sampling time affects both markers, with the lowest urinary concentrations obtained when samples were taken early in the morning. Both creatinine and the Cr-EDTA complex produce similar estimates of urine volume. However, despite the greater precision of the estimates obtained with chromium, the values obtained with creatinine exhibited less bias and are, therefore, more accurate.
Keywords: Chromium; metabolism trials; urinary excretion